2022
DOI: 10.1038/s41598-022-14690-0
|View full text |Cite
|
Sign up to set email alerts
|

A set of gene knockouts as a resource for global lipidomic changes

Abstract: Enzyme specificity in lipid metabolic pathways often remains unresolved at the lipid species level, which is needed to link lipidomic molecular phenotypes with their protein counterparts to construct functional pathway maps. We created lipidomic profiles of 23 gene knockouts in a proof-of-concept study based on a CRISPR/Cas9 knockout screen in mammalian cells. This results in a lipidomic resource across 24 lipid classes. We highlight lipid species phenotypes of multiple knockout cell lines compared to a contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 85 publications
2
6
0
Order By: Relevance
“…In a very recent study, Spiegel et al characterised the lipidomic changes of a set of gene knockouts, including DECR2, in a colon cancer cell line. The authors observed elevated levels of long-chain PUFAs in PI, PE-O and PC-O lipid classes (C20 and C22), confirming previous studies that DECR2 can oxidise unsaturated fatty acids and assist in the degradation of PUFAs such as arachidonic acid (AHA) and DHA in peroxisomes 45 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In a very recent study, Spiegel et al characterised the lipidomic changes of a set of gene knockouts, including DECR2, in a colon cancer cell line. The authors observed elevated levels of long-chain PUFAs in PI, PE-O and PC-O lipid classes (C20 and C22), confirming previous studies that DECR2 can oxidise unsaturated fatty acids and assist in the degradation of PUFAs such as arachidonic acid (AHA) and DHA in peroxisomes 45 .…”
Section: Discussionsupporting
confidence: 82%
“…Although upon examination of the crystal structure of DECR2 showed selectivity for VLCFAs like docosahexaenoic acid (DHA) 43 , another study reported that DECR2 may be involved in the degradation of short and medium chain substrates 44 . In a very recent study, Spiegel et al and DHA in peroxisomes 45 .…”
Section: Peroxisomal β-Oxidation (Perfao) Is An Understudied Aspect O...mentioning
confidence: 93%
“…In a very recent study, Spiegel et al characterised the lipidomic changes of a set of gene knockouts, including DECR2, in a colon cancer cell line. The authors observed elevated levels of long-chain PUFAs in PI, PE-O and PC-O lipid classes (C20 and C22), confirming previous studies that DECR2 can oxidise unsaturated fatty acids and assist in the degradation of PUFAs such as arachidonic acid (AHA) and DHA in peroxisomes [ 37 ]. Accordingly, our data demonstrated that DECR2 knockdown and TDZ treatment increased the levels of several acylcarnitine species in cells supplemented with DHA, indicating inhibition of perFAO.…”
Section: Discussionsupporting
confidence: 80%
“…LPCAT3 has LPEAT and LPCAT activity, while AGPAT3 (LPAAT) catalyzes LPA reactions 33 . To further examine the general applicability of our method, a dataset containing multiple gene knockouts in lipid metabolic pathways was also used to assess the performance of iLipdiome 57 . Overall, the top 5 perturbed pathways across 11 gene knockouts revealed by iLipidome were highly consistent with the enzyme specificities and the expected lipidomic changes affected by each knockout ( Extended Data Table 1 ).…”
Section: Discussionmentioning
confidence: 99%